Illuminations - Benjamin, Walter (The Bodley Head Ltd, 2015)
"Walter Benjamin was one of the most original cultural critics of the twentieth century. Illuminations includes his views on Kafka, with whom he felt a close personal affinity; his studies on Baudelaire and Proust; and his essays on Leskov and on Brecht's epic theater. Also included are his penetrating study "The Work of Art in the Age of Mechanical Reproduction," an enlightening discussion of translation as a literary mode, and Benjamin's theses on the philosophy of history. Hannah Arendt selected the essays for this volume and introduces them with a classic essay about Benjamin's life in dark times. Also included is a preface by Leon Wieseltier that explores Benjamin's continued relevance for our times."